Labour Market in Ukraine: an Empirical Dynamic Analysis Using Error Correction Model - Lukyanenko, І.; Oliskevych, M. (Київський національний університет імені Тараса Шевченка, 2014)
The labor market background in Ukraine has not only economic but also significant social value, and therefore is an important element of social and economic policy. The effectiveness of the state socio-economic regulation mechanisms requires profound analysis, modeling and forecasting of the processes of the labor market by means of modemn flexible econometric tools, taking into account фе short-term dynamics of economic processes and features that are characteristic of фе unstable economic development of ourcountry. As а result of empirical research on relationships between the macroeconomic indicators of the labor market in Ukraine, we developed a set of dynamic econometric models using an error-correction mechanism which take into account the long-run equilibrium relationships, as well as provide an opportunity to model the short-term effects of several factors such as the rate of change of wages, size of the labor force, employment and unemployment. The developed model is used to predict future trends of the labor market, as well as to describe the dynamics of its operation under various alternative scenarios of economic development. The application of the developed specifications in the structure of an integral macroeconometric model of Ukraine will allow us to carry out а comprehensive analysis of economic processes in the national economy and its prospects both in the short term and in the long run.

У результаті емпіричного дослідження взаємозв'язків між основними макропоказниками функціонування ринку праці в Україні pos: роблено комплекс динамічних економетричних моделей 3 використанням механізму корегування похибок. Оцінено довгострокові рівноважні зв'язки та короткострокові ефекти впливу низки чинників. Здійснено прогнозування майбутніх тенденцій на ринку праці, а також проаналі зовано різні альтернативні сценарії розвитку економіки.
Ринок праці в Україні: емпіричний динамічний аналіз з використанням моделі корегування похибки
Keywords: labour market; econometric modeling; error-correction model; wage; employment; unemployment; scenarios of development; forecasting; ринок праці; економетрична модель корегування помилки; сценарії розвитку; прогнозування